Effectiveness of a web-based foot-ankle exercise program for treating ulcer risk factors in diabetic neuropathy in a randomized controlled trial - Jane S. S. P. Ferreira; Ronaldo H. Cruvinel-Júnior; Erica Q. da Silva; Jady L. Veríssimo; Renan L. Monteiro; Marcos Duarte; Claudia Giacomozzi; Isabel C. N. Sacco (Scientific Reports)
Abstract The need for strategies to prevent complications from diabetic neuropathy (DPN) is well recognized. However, foot-ankle exercise programs show weak to moderate evidence, and barriers to their implementation persist, including broad and facilitated access to exercise programs, which guarantee for equity. In this paper, we report for the first time the effectiveness of a web-based foot-ankle exercise program aiming to improve DPN-related outcomes, gait biomechanics and functional outcomes. Sixty-two participants with DPN were randomly allocated into the control group (CG; n = 31), which received the usual care, or the intervention group (IG; n = 31), which received the usual care plus a 12-week foot-ankle exercise program using a web-based software (the SOPeD software). The primary outcomes, DPN symptoms and severity, were assessed using the Brazilian version of the Michigan Neuropathy Screening Instrument and the Decision Support System for Classification of Diabetic Polyneuropathy, respectively. Secondary outcomes included tactile sensitivity (monofilaments) and vibration perception (tuning fork), functional outcomes, such as foot pain and function (Foot Health Status Questionnaire), foot muscle strength and plantar pressure during gait (emed plate), and foot-ankle kinematics and kinetics during gait. Outcomes were assessed at baseline, 12 and 24 weeks by an assessor blinded to group allocation. DPN symptoms and severity remained unchanged after the web-based foot-ankle program. However, IG showed improvements compared to CG, with greater functional reach at 12 weeks, better foot function, reduced foot pain and greater plantarflexion degree during push-off at 24 weeks. Regarding plantar loading during gait, the forefoot pressure reduced in the IG at 12 weeks compared to baseline, but at 24 weeks, forefoot load increased in the IG compared to CG. The 12-week web-based foot-ankle exercise program was feasible, acceptable, demonstrating safety with minimal adverse events, such as delayed onset muscle soreness and foot muscle cramping. While DPN-related outcomes were unaffected by the 12-week SOPeD program, modest improvements in foot pain and function, functional reach, and changes in plantar pressure and plantarflexion degree during gait were noted, mostly at 24 weeks. Trial registration: ClinicalTrials.gov, NCT04011267. Registered on 8 July 2019.